How a Coriolis mass flow meter can operate in two-phase (gas/liquid) flow - Henry, M; Duta, M; Tombs, M; Yeung, H; Mattar, W (International Society of Automation, 2004)
It has been well documented over many years that Coriolis mass flow meters are unable to perform well when presented with two-phase (gas/liquid) flow. There are two aspects to the problem: it can be difficult to maintain flowtube oscillation at higher levels of two-phase flow (typically 2-20% of gas by volume), and even at low levels of gas entrainment, where the flowtube continues to resonate, mass flow errors can be severe. This paper provides an overview of how to provide good Coriolis mass flow and density measurements in two-phase flow, and explains the central role of the flowtube drive control system. Two classes of application having widespread industrial significance are addressed: the problem of batching to or from an empty Coriolis flowtube, and dealing with continuous two-phase flow. Copyright 2004 by ISA - The Instrumentation, Systems and Automation Society.